Physiologic correlates to running performance in pre-pubertal distance runners - Unnithan, V. B.; Timmons, J. A.; Paton, J. Y.; Rowland, T. W. (International Journal of Sports Medicine, 1995)
In adults, four major variables have been shown to be associated with success in distance running performance: submaximal oxygen consumption (running economy), peak oxygen consumption (Peak VO2), ventilatory threshold (VT) and fractional utilisation (FU). The primary aim of this study was to describe the relationship between the 3000 m race times of run-trained prepubertal boys to these four variables. Thirteen male run-trained pre-pubertal boys (age 11.7 +/- 1.1 yrs, mean +/- SD), volunteered to take part in a 3000 m time trial and laboratory assessment, consisting of treadmill running at four submaximal speeds (8, 9.6, 11.2 and 12.8 km.h-1) as well as a peak VO2 test. The group demonstrated a heterogeneous array of peak VO2 data. A high level of association (p < 0.05) was found between mass-relative peak VO2 and 3000 m time trial results (r = -0.83). In addition ventilatory threshold expressed as %peak VO2, VO2 at VT and estimated velocity at VT was also highly related to 3000 m time trial (r = -0.78, -0.77 and -0.77) respectively. Fractional utilisation (%peak VO2) was significantly (p < 0.05) associated with race time at the final two submaximal running speeds only (11.2 and 12.8 km.h-1) (r = 0.61 and 0.67, respectively). Respiratory Exchange Ratio (RER) was also found to be significantly (p < 0.05) associated with 3000 m race time at 11.2 and 12.8 km.h-1. Overall peak VO2 appeared to be the single most important factor associated with success at 3000 m.